Crucial steps in the structure determination of a coronavirus spike glycoprotein using cryo‐electron microscopy - Walls, Alexandra (Protein Sci, 2016)
The tremendous pandemic potential of coronaviruses was demonstrated twice in the last 15 years by two global outbreaks of deadly pneumonia. Entry of coronaviruses into cells is mediated by the transmembrane spike glycoprotein S, which forms a trimer carrying receptor‐binding and membrane fusion functions. Despite their biomedical importance, coronavirus S glycoproteins have proven difficult targets for structural characterization, precluding high‐resolution studies of the biologically relevant trimer. Recent technological developments in single particle cryo‐electron microscopy allowed us to determine the first structure of a coronavirus S glycoprotein trimer which provided a framework to understand the mechanisms of viral entry and suggested potential inhibition strategies for this family of viruses. Here, we describe the key factors that enabled this breakthrough.